Age Predicts Disruption of the Articular Surface of the Femoral Condyles in Knee OCD: Can We Reduce Usage of Arthroscopy and MRI?. Issue 3 (March 2018) - Siegall, Evan; Faust, John R.; Herzog, Mackenzie M.; Marshall, Kelley W.; Willimon, S. Clifton; Busch, Michael T.
Abstract : Background: The purpose of this study was to determine if patient age could accurately identify disrupted articular cartilage overlying an osteochondritis dissecans (OCD) lesion of the femoral condyle in adolescents. This could have important implications for imaging and treatment decisions. Methods: All patients from 2001 to 2014 who were arthroscopically treated for a femoral condyle OCD were included in this Institutional Review Board-approved study. Exclusion criteria were trochlear and patellar OCD lesions, idiopathic arthritis, and traumatic osteochondral injuries. Arthroscopy was performed to visualize and probe the articular surface. Arthroscopic and magnetic resonance imaging (MRI) findings were recorded as "intact" or "disrupted" cartilage. Extra-articular drilling was performed when the articular cartilage was intact. Results: There were 119 patients (81 male, 68%) with 139 OCD lesions in 136 knees. The mean age at time of surgery was 13.0 years (range, 7.2 to 19.3 y). At arthroscopy, 115 knees had intact cartilage and 24 had disrupted cartilage. There was a significant difference in age between patients with intact versus disrupted cartilage at arthroscopy (12.5 vs. 15.3 y; P <0.0001). Eighty-eight OCD lesions had MRIs preoperatively, showing 69 as intact and 19 (24%) disrupted. MRI reading for cartilage status had 94% sensitivity and 97% specificity. Multivariable regression analysis revealed that age ( P <0.01) and MRI status ( P <0.0001) were strong predictors of cartilage status. Sixteen years was the critical age in which both sensitivity was maximized and false positive probability was minimized. Over the age of 17 years, 7 of 7 (100%) had disrupted cartilage. Age alone was 100% sensitive for children below the age of 10, and 96% sensitive below the age of 13. Conclusions: Age was a good predictor of cartilage status in both younger (<13 y) and older (≥17 y) patients in this study. For patients in the mid-range group (13 through 16 y), age alone is not an adequate predictor of cartilage status, but adding MRI increased accuracy. Significance: Age can be used to stratify patients and thereby influence diagnostic and treatment strategies. Level of Evidence: Level IV.